Internal audit effectiveness and whistleblowing practice in Malaysia - Nor Raihana Asmar Mohd Noor
News of high-profile corruptions and financial malpractices continue to attract attention and become media headlines. Whether in the private or government sector, corruptions, financial misconduct and malpractices are usually associated with auditing weaknesses and ineffective internal control systems. Various initiatives have been developed to reduce the negative perception of public sector frauds including the establishment of internal audit department in every government agency. However, to date, it is still questionable whether the internal audit is efficient and effective due to the rising reported frauds cases in government departments. Literatures related to the effectiveness of internal audit are still lacking especially concerning the internal audit of government departments. Thus, this study was conducted to determine the effects of four determinants of internal audit effectiveness in the public sector which are internal audit independence, internal audit quality, proficiency of internal auditors and scope of audit. In addition, this research also examined the practice of whistleblowing as a mediating variable in the relationships between the independent and dependent variables. The theoretical framework of this study is supported by two underpinning theories which are Institutional Theory and Justice Theory. A mixed method design was employed in this research. In the first stage, a survey was conducted involving 203 internal auditors, selected by convenience and purposive sampling. Data for this phase was analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). In the second stage, three key informants were interviewed. They were selected using purposive sampling and data were analysed using deductive and inductive approaches. Two key findings emerged from data analyses. First, internal audit independence, internal audit quality, proficiency of internal auditors and scope of audit each has a significant positive effect on the effectiveness of internal audit. Second, the study confirmed the mediating effect of the practice of whistleblowing on the relationship between scope of audit and the effectiveness of internal audit. However, the practice of whistleblowing did not mediate other examined relationships. Overall, the findings have advanced prior research by providing new insights on the determining factors that can potentially improve the effectiveness of internal audit. Other than theoretical contribution, this study also offers several policies and practical implications. The Malaysian government needs to improve the public sector audit to enhance its effectiveness and strengthen the existing regulatory framework for public sector audit. A new theme was also derived from the qualitative approach which suggests that management support should be given in financial and non-financial aspects. Limitations of this study and suggestions for future research were discussed in the final section of the thesis.